POKET PERIODONTAL PADA BURUH PEROKOK - Saptorini, Kriswiharsi Kun; Kusuma, Agus Perry (Fakultas Kedokteran Gigi Universitas Jember, 2013)
Background. Periodontal disease is a disease of the tissues supporting the teeth. Clinical signs of periodontitis is the presence of gingival inflammation, swelling interdental papillae, formation of pocket / gingival pocket and gingival recession. The increase of periodontal disease prevalence in smokers caused by poor oral hygiene and late diagnosis.Method. Reseach objective was to prove the factors that related to periodontal pocket. Study design was cross-sectional. The study population were 85 labours of loading and unloading at the Port of Tanjung Emas Semarang, the collection of data through interviews and clinical observations. Data were analyzed by chi-square test with 95 % Confidence Interval and Prevalence Ratio were calculated. Results. The results showed all respondents have periodontal pocket with an average depth of pocket were 1.4 mm. The proportion of periodontal pocket depth more than 1.4 mm (50.6%) and less than 1.4 mm (49.4%) were almost comparable. Factors significantly associated with periodontal pocket were the duration of smoking (p-value 0.04, 95% CI = 1.037 to 5.941; PR = 2.482), oral hygiene (p-value 0.023, 95% CI = 1.143 - 13.311; PR = 3.9), and saliva buffer capacity (p-value 0.011, 95% CI = 1.283 to 7.984; PR = 3.2). Conclusion. Smoke have a greater risk of periodontal pocket, therefore smokers should be given health education on dental and oral health maintenance in the form of brushing and regular dental plaque cleaning (scaling). Smokers need to reduce the number of cigarettes that smoked or quit smoking.